Perspectives on outpatient administration of CAR-T cell therapy in aggressive B-cell lymphoma and acute lymphoblastic leukemia. Issue 4 (12th April 2021) - Myers, G Doug; Verneris, Michael R; Goy, Andre; Maziarz, Richard T
Abstract : Chimeric antigen receptor (CAR) T-cell therapies that specifically target the CD19 antigen have emerged as a highly effective treatment option in patients with refractory B-cell hematological malignancies. Safety and efficacy outcomes from the pivotal prospective clinical trials of axicabtagene ciloleucel, tisagenlecleucel and lisocabtagene maraleucel and the retrospective, postmarketing, real-world analyses have confirmed high response rates and durable remissions in patients who had failed multiple lines of therapy and had no meaningful treatment options. Although initially administered in the inpatient setting, there has been a growing interest in delivering CAR-T cell therapy in the outpatient setting; however, this has not been adopted as standard clinical practice for multiple reasons, including logistic and reimbursement issues. CAR-T cell therapy requires a multidisciplinary approach and coordination, particularly if given in an outpatient setting. The ability to monitor patients closely is necessary and proper protocols must be established to respond to clinical changes to ensure efficient, effective and rapid evaluation either in the clinic or emergency department for management decisions regarding fever, sepsis, cytokine release syndrome and neurological events, specifically immune effector cell-associated neurotoxicity syndrome. This review presents the authors' institutional experience with the preparation and delivery of outpatient CD19-directed CAR-T cell therapy.